Probability of occurrence of high temperature events during reproductive phase of wheat in Punjab - KRITI GUPTA; S. S. SANDHU; PRABHJYOT-KAUR; K. K. GILL (Journal of Agrometeorology)
A study was conducted with an objective to analyze how often high temperature events occur during the reproductive phases of wheat (January-March) in Punjab. Historical temperature data was analyzed to understand the probability of occurrence of temperature higher than the mean and its different combinations (mean+0.5SD, mean+1.0SD, mean+1.5SD and mean+2SD) during different standard meteorological weeks (SMW). It was found that at Ludhiana (central Punjab) the highest probability of maximum temperature (Tmax) and minimum temperature (Tmin) being higher than range was 16.9% and 18.8% during 9th and 4th SMW, respectively. At Ballowal Saunkhri (northeastern Punjab) the maximum probability of occurrence of Tmax higher than range was 16.4% during 6th and 12th SMW, respectively and that for Tmin higher than range was 20% during 9th SMW. At Bathinda (southwestern Punjab) the highest probability of occurrence of Tmax and Tmin above range was 19.7% and 19.4% during 13th and 11th SMW, respectively. In northeastern and southwestern regions of Punjab the probability of having Tmax and Tmin above range was maximum during 12-13th and 9th-11th SMW, respectively, while in central region it was maximum during 9th and 4th SMW, respectively. This implies that wheat crop should be managed adequately during these periods to avoid damage due to heat stress.